Foreign devils and philosophers (Leiden ; Boston)
xiv, 376 sayfa
Keywords: “What was the cultural impact of early meetings between Chinese and Europeans? This book explores visual, literary, and scholarly representations of the Celestial Empire and Western countries against the backdrop of actual encounters. Based on rare Chinese and, correspondingly, European (especially Dutch) sources and archival documents, the volume covers a range of cultural expressions from the applied arts to philosophy. Special attention goes to the ideals and realities of trade and diplomacy of the Dutch East India Company in China. 'Foreign Devils and Philosophers' approaches global history from a cultural perspective and illuminates the reciprocal dynamic of aversion and admiration: Chinese and Westerners could appear as sages or savages in each other's eyes.” --